Role of Digital Economy in Rebuilding and Sustaining the Space Governance Mechanisms - Cai, Cen; Qiu, Ran; Tu, Yongqian (Frontiers in Psychology, 2022)
The need for sustainable corporate governance has gained the interests of researchers for a while now and it has been found as a very significant component of successful organizational operations. The current paper has examined the role of sustainable corporate governance in achieving sustainable economic space along with measuring the indirect impact of technological innovation and IT governance on the whole process. This paper has followed the quantitative-positivism approach to measure the hypotheses developed in the study. The population considered in this study are the managers currently employed in the corporate sector in China (N = 310). The data is analyzed using the Smart-PLS 3.3.3 software for checking the data for preliminary screening and the measurement of hypotheses. The findings of the study show that the three components of sustainable corporate governance, i.e., concern for employees, sustainable corporate governance awareness, and the environmental aspects have a significant as well as a positive effect on technological innovation and hence on the sustainable economic space. Similarly, the study has recorded a significant moderating effect of IT governance on the relationship of technological innovation and the sustainable economic space. Overall, it can be seen that corporate governance, innovative technology, and a sustainable digital economy share a reciprocal relationship. Where corporate governance helps as a supporting force to keep both innovation and sustainability in action. Whereas IT governance provides enhanced communication and delivery of public services, business, and advanced human capital. The study will be of high advantage for the corporate sector in China for devising and modifying their policies that consider the employee’s concerns for the governance mechanisms prevailing at priority in the organizations. Further, it will be interesting for the organizations to incorporate the IT governance mechanism in their technological innovations for achieving a sustainable economic space.